2021
DOI: 10.1186/s12866-021-02123-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term stability of the urogenital microbiota of asymptomatic European women

Abstract: Background To date, information on healthy female urinary microbiota is available mostly at genus level and at one time point. However, profound species-level characterization of healthy urinary microbiome and its stability over time are essential for further correct interpretation of its role in healthy urogenital tract. In this study, we investigated female urogenital microbiome (FUM) at two timepoints (within 2.5-year interval) in young asymptomatic European women. We used culturomics with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 41 publications
2
33
0
Order By: Relevance
“…Importantly, these studies collected urine by catheterization or suprapubic needle aspiration to limit vaginal contamination of urine specimens, supporting the conclusion that Gardnerella can indeed be found within the bladder. In a recent longitudinal culturomics study of healthy women, Gardnerella was often present at high relative abundance in urine sample pairs collected from the same woman at different time points ( Ksiezarek et al., 2021 ). Another large study found hospital inpatients with G. vaginalis in their urine were more likely to have a history of rUTI than patients in whom G. vaginalis was not detected ( Josephson et al., 1988 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, these studies collected urine by catheterization or suprapubic needle aspiration to limit vaginal contamination of urine specimens, supporting the conclusion that Gardnerella can indeed be found within the bladder. In a recent longitudinal culturomics study of healthy women, Gardnerella was often present at high relative abundance in urine sample pairs collected from the same woman at different time points ( Ksiezarek et al., 2021 ). Another large study found hospital inpatients with G. vaginalis in their urine were more likely to have a history of rUTI than patients in whom G. vaginalis was not detected ( Josephson et al., 1988 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, 127 OTUs were detected in vaginal and anal samples of the same subjects. Most of these OTUs were components of the female urogenital microbiota, such as Lactobacillus, Gardnerella, Streptococcus, Staphylococcus, Corynebacterium, and E. coli [17]. It is noteworthy that no significant differences in the number of OTUs shared in VS and AS were found based on the presence or absence of CT.…”
Section: Taxonomic Composition Of Vaginal and Anal Bacterial Communitiesmentioning
confidence: 90%
“…Among them, 127 OTUs were detected in vaginal and anal samples of the same subjects. Most of these OTUs were components of the female urogenital microbiota, such as Lactobacillus, Gardnerella, Streptococcus, Staphylococcus, Corynebacterium, and E. coli [17]. It is noteworthy that no significant In anal metagenomes (Figures 3b and S4), Enterococcus (E. faecalis and E. durans), Escherichia-Shigella, and Parasutterella were more abundant in AS−, while Desulfovibrio, Parvimonas, and Pseudomonas were more abundant in AS+.…”
Section: Taxonomic Composition Of Vaginal and Anal Bacterial Communitiesmentioning
confidence: 97%
“…GenBank accession numbers and species identification for FUM isolates subjected to Sanger sequencing are available in Supplementary Table S2 and previously published by Ksiezarek et al . (17). Phylogenetic analysis based on individual genes were performed to access putative novel species by using MEGA version 7.0 (21), constructed according to neighbour-joining method (22), and genetic distances were estimated using Kimura’s 2-parameter model (23).…”
Section: Methodsmentioning
confidence: 99%
“…Available studies point to dominance of e.g., Lactobacillus crispatus, Lactobacillus jensenii , and Gardnerella spp. (often mistakenly reported as Gardnerella vaginalis ) (15), and the presence of certain potential uropathogens such as Escherichia coli and Enterococcus faecalis, usually observed in low amounts (7, 13, 16, 17). In fact, detailed species-level characterization is essential to understand FUM diversity and identify key functions contributing to urinary health and disease, since specific features are often species- or even strain-specific.…”
Section: Introductionmentioning
confidence: 99%